2020
DOI: 10.22146/ijc.49842
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Characterization and Biological Efficacies from Some New Dinuclear Metal Complexes for Base 3-(3,4-Dihydroxy-phenyl)-2-[(2-hydroxy-3-methylperoxy-benzylidene)-amino]-2-methyl Propionic Acid

Abstract: The reaction of methyldopa with o-vanillin in refluxing ethanol afforded Schiff base and characterized through physical analysis with a number of spectra also the study of biological activity. The geometry of the Schiff base was identified through using (C.H.N) analysis, Mass, 1H-NMR, FT-IR, UV-Vis spectroscopy. Metal complexes of Cr3+, Mn2+, Co2+, Ni2+, Cu2+, Zn2+, Cd2+ and Hg2+ with Schiff base have been prepared in the molar ratio 2:1 (Metal:L), (L = Schiff base ligand) except Hg2+ at molar ratio 1:1 (Hg:L)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 18 publications
0
17
0
Order By: Relevance
“…[22][23][24] In addition, earlier study has shown that in the presence of transition metals, the azo-dye nitrogen is always more likely to favor complexation. 25,26 It was difficult to confirm that the Co(II)complex was engaged in chelate formation due to the presence of coordinated water molecules. The existence of OH bands in the IR spectra of Co(II) complex in the 3423 cm1 region was attributed to the presence of coordinated water molecules in the coordination sphere.…”
Section: Liquid Chromatography-mass Spectrometry (Lc-ms) Measurementsmentioning
confidence: 99%
“…[22][23][24] In addition, earlier study has shown that in the presence of transition metals, the azo-dye nitrogen is always more likely to favor complexation. 25,26 It was difficult to confirm that the Co(II)complex was engaged in chelate formation due to the presence of coordinated water molecules. The existence of OH bands in the IR spectra of Co(II) complex in the 3423 cm1 region was attributed to the presence of coordinated water molecules in the coordination sphere.…”
Section: Liquid Chromatography-mass Spectrometry (Lc-ms) Measurementsmentioning
confidence: 99%
“…As shown in the tables, the disappearance of the bands in the range 3419-3481 cm -1 belonging to the hydroxyl phenolic (O) complexes is evidence of its chelation by the phenolic oxygen atom [13]. The bending (Wagging and twisting) of the coordination water complexes appears by about 623-757 cm -1 [14]. The linked nitrogen atom of thiadiazol ring shows shifted absorption bands of ligand at 1174-1303 cm -1 in complexes confirming the metal's binding to the by group =N-N= [15].…”
Section: Ft-ir Spectra Of Complexesmentioning
confidence: 99%
“…In addition, two new absorption peaks at (456 and 575) nm are attributed to transitions type 1 A1g→ 1 T2g, 1 A1g→ 1 T1g, respectively of Pt(IV) complex. It was indicative of octahedral geometry [20,21]. The electronic absorption of [Au (L)(H2O)Cl] peaks at (285) nm is ascribed to the π⟶π*, and (442) nm, (578) nm are ascribed to the 1 A1g→ 1 B1g, 1 A1g→ 1 A2g, respectively, which are a good evidence for square planer geometry [22], electronic transition, magnetic moments, and suggested formula of metal complexes given in Table 3.…”
Section: Electronic Transitionmentioning
confidence: 78%